Antibacterial Susceptibilty of PhilNONI Juice versus Salmonella typhi, Staphylococcus aureus, and Escherichia coli - Maslog, Florita S. (Silliman Journal, 2023)
Juice extracted from noni fruit (Morinda citrifolia, Linn) is a natural dietary supplement that has been claimed to benefit human health. Limited clinical tests from medical doctors and food scientists all over the world have testified to its beneficial effects. The secret in health giving power lies in the number and variety of components found in the noni fruit. A scientific approach to understanding the phenomenon why and how it has become a popular dietary supplement, as a functional food, or as a natural health enhancer is due to the fact that Morinda citrifolia contains phytochemicals that own antibacterial, antiviral, antifungal, antitumor, anti-helmintic, analgesic, hypotensive, anti-inflammatory, and immune- enhancing effect (Maslog, 2014). This in-vitro study focuses on the inhibitory effect of M. citrifolia juice using the branded product,100% PhilNONI Juice, of a local company, Phil Morinda Citrifolia Inc. (PMCI), versus pathogenic microorganisms Salmonella typhi, Staphylococcus aureus and Escherichia coli. Two methods were used in determining the antimicrobial susceptibility of PhilNONI Juice: one is to find out the minimum inhibitory concentration (MIC) by the tube dilution method and the second is the determination of the juice’s antibacterial activity against these pathogenic organisms assessed by the presence or absence of growth by the streak method with the pathogenic organisms by Todd, Sanford, Davidsohn (Henry, 1979). The study proved that 100% PhilNONI Juice has a potent antibacterial activity against Salmonella typhi, Staphylococci aureus and Escherichia coli based on the same pattern of antimicrobial susceptibility of standard chloramphenicol on these pathogenic organisms.